Tectonic Characteristics of Source Areas from Beach Sands of Tierra del Fuego and the Antartic Peninsule, Argentina - GELOS, EDGARDO MARTÍN; SPAGNUOLO, JORGE OSVALDO; ISLA, FEDERICO IGNACIO (Pesquisas em Geociências, 2000)
Sand mineralogical analysis from 22 beaches were performed within the southernmost area of Argentina (Isla Grande de Tierra del Fuego), the Antarctic Peninsula and the Scotia Arc (South Orkney, South Shetland and James Ross islands included). Composition triangles of light and heavy minerals were considered in order to relate them to depocenters, sediment sources and tectonic setting. 71% of the sediments would have been transported from magmatic arcs, 24% from elevated crystalline basements and only 5% from recycled orogene. In regard to the heavy mineral distribution, 70% were assigned to a suite from an active continental margin and the remaining 30% would correspond to areas outside the continental margins (volcanic arcs). In a general way, sediment sources were related to active margins or volcanic island arcs. As an anomalous fact, it is stressed that the coasts of Tierra del Fuego and the western sector of the Antarctic Peninsula and adjacent islands, contain sediments from a Pacific margin but lying on a passive Atlantic margin. Finally, it should be adviced about the convenience to know the source areas when ice is the transport agent, as it avoids a selective ability and it does not modify the original mineralogical composition.